2023
DOI: 10.21203/rs.3.rs-2586153/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vis-NIR-SWIR spectroscopy in mapping of soil physical-chemical attributes in areas cultivated with irrigated mango in the Brazilian semi-arid region

Abstract: The adoption of specific soil management in agricultural areas requires a series of soil analyses, which is time-consuming and costly. In this context, Vis-NIR-SWIR spectroscopy (visible - near infrared - short-wave infrared) emerges as an alternative to determine soil attributes quickly, with lower cost and few environmental impacts. Thus, the objective of this study was to map the physical-chemical attributes of the soil in areas cultivated with irrigated mango in different soil classes in the Brazilian semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Carbon stock or storage in soil presents relevance for both environmental and agricultural contexts, and has been explored by means of portable MIR spectroscopy in vineyard soils, achieving reliable results for varying geopedological conditions [24]. Soil carbon stock was also mapped via near-infrared spectroscopy in a desertifi cation region from northeastern Brazil, a work in which the authors indicated that this technology could be used by government agencies for environmental monitoring [25]. The estimation of Soil Inorganic Carbon (SIC) is also an interesting approach which has been undertaken in the Vis-NIR range, coupling variable selection algorithms and deep learning methods, detecting SIC content quickly and accurately [26].…”
Section: Soil Carbonmentioning
confidence: 99%
“…Carbon stock or storage in soil presents relevance for both environmental and agricultural contexts, and has been explored by means of portable MIR spectroscopy in vineyard soils, achieving reliable results for varying geopedological conditions [24]. Soil carbon stock was also mapped via near-infrared spectroscopy in a desertifi cation region from northeastern Brazil, a work in which the authors indicated that this technology could be used by government agencies for environmental monitoring [25]. The estimation of Soil Inorganic Carbon (SIC) is also an interesting approach which has been undertaken in the Vis-NIR range, coupling variable selection algorithms and deep learning methods, detecting SIC content quickly and accurately [26].…”
Section: Soil Carbonmentioning
confidence: 99%